Biopolymer gene discovery and characterization using metagenomic libraries - Ohlhoff, Colin Walter (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Genetics. Institute of Plant Biotechnology))--Stellenbosch University, 2008.